Employment Policies and the Problem of International Balance - Kaldor, N. (Review of Economic Studies, 1951)
Journal Article Employment Policies and the Problem of International Balance Get access N. Kaldor N. Kaldor Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 19, Issue 1, 1950, Pages 42–49, https://doi.org/10.2307/2296270 Published: 01 December 1950